2003
DOI: 10.1073/pnas.1534745100
|View full text |Cite
|
Sign up to set email alerts
|

Gleevec inhibits β-amyloid production but not Notch cleavage

Abstract: Amyloid-␤ (A␤) peptides, consisting mainly of 40 and 42 aa (A␤40 and A␤42, respectively), are metabolites of the amyloid precursor protein and are believed to be major pathological determinants of Alzheimer's disease. The proteolytic cleavages that form the A␤ N and C termini are catalyzed by ␤-secretase and ␥-secretase, respectively. Here we demonstrate that ␥-secretase generation of A␤ in an N2a cell-free system is ATP dependent. In addition, the Abl kinase inhibitor imatinib mesylate (Gleevec, or STI571), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
159
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(177 citation statements)
references
References 40 publications
17
159
1
Order By: Relevance
“…This may reflect subtle variations between the cellular and in vitro conformations of ␥-secretase. Nevertheless, the cell-based studies confirmed that CS-1 maintains a preference for inhibition of the ␥-secretase mediated production of A␤42 over A␤40 or A␤38, which is distinct from previously reported GSMs (17) and inhibitors (14,15,18).…”
Section: Di-coumarin Compounds Are Selective Gsis In Cellssupporting
confidence: 40%
See 2 more Smart Citations
“…This may reflect subtle variations between the cellular and in vitro conformations of ␥-secretase. Nevertheless, the cell-based studies confirmed that CS-1 maintains a preference for inhibition of the ␥-secretase mediated production of A␤42 over A␤40 or A␤38, which is distinct from previously reported GSMs (17) and inhibitors (14,15,18).…”
Section: Di-coumarin Compounds Are Selective Gsis In Cellssupporting
confidence: 40%
“…Furthermore, these coumarin-dimer compounds similarly affect ␥-secretase activity for A␤40 and A␤38 production and lack the interconnected effect witnessed with the GSMs in which decreased A␤42 resulted in increased A␤38 generation, and vice versa (17). Therefore, these AGSIs represent a class of inhibitors that are distinct from the GSMs (12,17) as well as previously reported GSIs (14,15,18). It is noteworthy to point out that coumarin-dimer based compounds have been reported to be active against HIV integrase (32) and human NAD(P)H:quinine oxidoreductase-1 (33), as well as exhibit anticoagulant activity (34).…”
Section: Di-coumarin Inhibitors Alter the Sub-sites Of The ␥-Secretasmentioning
confidence: 66%
See 1 more Smart Citation
“…Additionally, it has been shown that imatinib inhibits the growth of PDGF-R-mediated glioblastoma cells 8 and sensitizes glioma cells to radiation-induced apoptosis. 9 The observation that imatinib inhibits the b-amyloid production in a cell culture model, which could make the inhibitor a useful basis for the development of a novel therapy for Alzheimer's disease, 10 points to a possible implication of imatinib also in neurodegenerative diseases. In line with this, we previously published that imatinib can induce the cellular clearance of prion-infected cells from PrP Sc , the pathological isoform of the cellular prion protein (PrP c ), by activating its lysosomal degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Incidentally, the pharmacological agent that inhibits GSAP has already been synthesized; this agent is the anti-cancer drug imatinib (also known as STI571 or Gleevec), which has been previously shown (by the same group [6] ) to inhibit γ-secretase activity. The biotinylated derivative of imatinib was used to isolate GSAP.…”
mentioning
confidence: 99%